The Plant Ribosome-Inactivating Proteins Play Important Roles in Defense against Pathogens and Insect Pest Attacks - Zhu, Feng; Zhou, Yang-Kai; Ji, Zhao-Lin; Chen, Xiao-Ren (Frontiers in Plant Science, 2018)
Ribosome-inactivating proteins (RIPs) are toxic N-glycosidases that depurinate eukaryotic and prokaryotic rRNAs, thereby arresting protein synthesis during translation. RIPs are widely found in various plant species and within different tissues. It is demonstrated in vitro and in transgenic plants that RIPs have been connected to defense by antifungal, antibacterial, antiviral and insecticidal activities. However, the mechanism of these effects is still not completely clear. There are a number of reviews of RIPs. However, there are no reviews on the biological functions of RIPs in defense against pathogens and insect pests. Therefore, in this report, we focused on the effect of RIPs from plants in defense against pathogens and insect pest attacks. First, we summarize the three different types of RIPs based on their physical properties. RIPs are generally distributed in plants. Then, we discuss the distribution of RIPs that are found in various plant species and in fungi, bacteria, algae and animals. Various RIPs have shown unique bioactive properties including antibacterial, antifungal, antiviral, and insecticidal activity. Finally, we divided the discussion into the biological roles of RIPs in defense against bacteria, fungi, viruses and insects. This review is focused on the role of plant RIPs in defense against bacteria, fungi, viruses and insect attacks. The role of plant RIPs in defense against pathogens and insects is being comprehended currently. Future study utilizing transgenic technology approaches to study the mechanisms of RIPs will undoubtedly generate a better comprehending of the role of plant RIPs in defense against pathogens and insects. Discovering additional crosstalk mechanisms between RIPs and phytohormones or reactive oxygen species (ROS) against pathogen and insect infections will be a significant subject in the field of biotic stress study. These studies are helpful in revealing significance of genetic control that can be beneficial to engineer crops tolerance to biotic stress.